Bayesian Theory and Methods with Applications - Savchuk, Vladimir; Tsokos, Chris P.; SpringerLink (Online service) (Paris : Atlantis Press, 2011)
Bayesian methods are growing more and more popular, finding new practical applications in the fields of health sciences, engineering, environmental sciences, business and economics and social sciences, among others. This book explores the use of Bayesian analysis in the statistical estimation of the unknown phenomenon of interest. The contents demonstrate that where such methods are applicable, they offer the best possible estimate of the unknown. Beyond presenting Bayesian theory and methods of analysis, the text is illustrated with a variety of applications to real world problems.
Keywords: Statistics; Computer science; Statistical methods; Mathematics; Mathematical statistics; Statistics; Statistical Theory and Methods; Applications of Mathematics; Mathematical Modeling and Industrial Mathematics; Probability and Statistics in Computer Science; Biostatistics; Popular Science in Mathematics/Computer Science/Natural Science/Technology.